Petrified child mummies by Paolo Gorini (19th century CE, Lodi, Lombardy, Italy): anthropological, pathological, and conservation perspectives - Larentis, Omar; Gorini, Ilaria; Campus, Michele; Vanin, Stefano; Tonina, Enrica; Carta, Giuseppina; Carli, Alberto; De Luca, Lisa; Piombino-Mascali, Dario (Frontiers in Medicine, 2025)
This study presents an interdisciplinary analysis of six non-adult petrified specimens prepared by the Italian scientist Paolo Gorini (1813–1881) in Lodi, Lombardy, during the 19th century. Housed since 1981 in the Old Hospital, these individuals represent the entire known corpus of Gorini’s preserved children. The research combined macroscopic inspection, radiographic imaging, anthropological assessment, and entomological observations to document biological characteristics, embalming techniques, and conservation needs. Radiographic analysis enabled the estimation of ages at death, ranging from approximately 1.5–12 months, and provided detailed information on skeletal development, dental formation, and pathological conditions. Soft tissues were preserved to an exceptional degree, allowing for the identification of dermal, muscular, and visceral structures. Notable modifications, such as intraorbital inserts, revealed Gorini’s attention to appearance and presentation. The results demonstrate the effectiveness of Gorini’s petrification process, now better understood through recent discoveries of his embalming formulae. His technique achieved both anatomical preservation and long-term stability, even in fragile non-adult individuals. Beyond technical achievements, the specimens reflect broader 19th-century cultural attitudes toward childhood, mortality, and commemoration in a period of elevated death rates. By integrating biological, historical, and conservation perspectives, this study contributes both to the documentation of a unique anatomical collection and to the safeguarding of its future. It also situates Gorini’s work within the scientific and cultural milieu of his time, highlighting the intersection of experimental anatomy, public display, and the desire for permanence over death.